Changing trends in the endourological management of urolithiasis in anomalous kidneys. (2nd November 2018) - Singh, Abhishek G.; Jairath, Ankush; Balaji, Sudharshan S.; Tak, Gopal; Ganpule, Arvind P.; Vijayakumar, Mohankumar; Sabnis, Ravindra B.; Desai, Mahesh R.
Abstract : Objectives: To present our single‐centre experience of urolithiasis management in anomalous kidneys, highlighting the need for an algorithm‐based approach in deciding the appropriate treatment method for each type. Patients and Methods: We retrospectively reviewed the data of all the patients who presented to our renal unit with urolithiasis in an anomalous kidney between January 1990 and July 2014. The peri‐operative characteristics of all the patients, along with management approach, were studied. Results: Percutaneous nephrolithotomy (PCNL) was the most common surgical technique used, followed by flexible ureterorenoscopy (URS). Pain was the most common presentation in these patients. The overall stone clearance rate associated with PCNL and flexible URS was 85.8% in cases of anomalous kidneys in this series. The stone clearance rates in ectopic kidneys, horseshoe kidneys, malrotated kidneys and autosomal dominant polycystic kidneys associated with PCNL and flexible URS were similar: 86%, 88%, 76% and 83%, respectively, and 81.2%, 80%, 92% and 100%, respectively . Based on our results, we developed a stone management algorithm. Conclusion: The management of renal calculi in patients with renal anomalies may vary based on the stone size, location, density, pelvicalyceal system anatomy and drainage. An algorithm‐based approach could help surgeons decide the appropriate treatment in this population.